Aspects of the ecology and management of the Soupfin shark (Galeorhinus galeus) in South Africa - McCord, Meaghen Erica (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2005)
Global trends in teleost fisheries indicate significant population declines. Thus, alternative fisheries are being developed to meet the growing economic and nutritional demands of the expanding human population. Recently, it has been established that elasmobranch fisheries may fulfill these demands. As many elasmobranchs possess life-history characteristics that make them particularly vulnerable to overfishing, it is imperative to develop management strategies prior to the inception of these fisheries to ensure sustainable resource utilisation. In South Africa, elasmobranchs have been commercially exploited since the 1930s. Although generally considered an under-exploited resource, the potential for growth within these fisheries has been recognized. In 2005, the commercial shark fishery will undergo a transition from medium to long-term rights allocations. This represents an ideal opportunity for scientists and managers to develop precautionary species-specific management plans for commercially exploitable elasmobranch species. The soupfin shark (Galeorhinus galeus) is one of the principal target species in South Africa's shark fisheries. Given its inherent susceptibility to overexploitation, G. galeus was selected as a management priority by South Africa's regional fisheries organisation. The purpose of this study was to examine and describe the stock status of G. galeus in South Africa, and to develop a precautionary fishery management plan to ensure the sustainability of this resource. Age, growth, and mortality calculations for G. galeus were made from research survey data collected between 1996 and 1999. A small sample size precluded independent analyses of females. The maximum recorded age for G. galeus was 33 years. Estimated von Bertalanffy growth parameters from observed length-at-age for males and combined sexes were: Lâˆž 1542.8 mm TL, K 0.21 yearâ »Â¹ , tâ‚€ -2.79 yearâ »Â¹ and Lâˆž 1560.3 mm TL, K 0.19 yearÂ¹, tâ‚€ -3.03 yearâ »Â¹, respectively. The age-at-50% maturity was determined to be 6 years, corresponding to 1011 mm TL for males and 1100 mm TL for combined sexes. Natural mortality was calculated as 0.126 yrâ »Â¹. The rate of instantaneous total mortality was calculated as 0.27 yrâ »Â¹. Catch trend analysis showed that catches and CPUE of G. galeus are increasing in the demersal longline fishery, and decreasing in the handline fishery. Decreasing catches and CPUE were observed in fishery-independent research survey data. The status of the soupfin shark stock was modelled using per-recruit analysis. The SB/R model indicated the soupfin shark is being optimally exploited and spawner biomass is at 43% of preexploitation levels. Current fishing levels ( F = 0.14 yrâ »Â¹) approximate the Fsbâ‚„â‚€ level (F = 0.17 yrÂ¹); thus, an increase in fishing pressure may lead to stock collapse. It was determined that the current age-at-capture (7.9 years) should be increased to 10 years, or 1420 mm TL, to maximize yield and minimize the possibility of recruitment failure. The results of this study indicate a need for immediate scientific and management intervention in South Africa's soupfin shark fishery. An assessment report and fishery management plan for G. galeus was compiled, and several management options were proposed. These include the implementation of licence and size restrictions, as well as seasonal/area closures. The potential for an experimental gillnet fishery should be investigated.
Keywords: Soupfin shark -- South Africa; Soupfin shark -- Ecology -- South Africa; Fishery management -- South Africa; Shark fisheries -- Management -- South Africa